Mecanismos de preservação do equilíbrio econômico-financeiro nas concessões rodoviárias federais - Souza, Ana Paula Peresi de (2022)
This study examines mechanisms that preserve the economic and financial balance of the Brazilian highway concession agreements. Act n. 8.987, from 1995, sets forth the key rules for these types of agreements. Nevertheless, it does not establish detailed rules on the economic and financial balance of those agreements. It falls on the contract to regulate the boundaries of this issue. The highway sector has been addressing this through contractual clauses that deepen the general rules set forth in the statutory law. The analysis of each of the twenty-six concession agreements, executed from 1994 to 2021, when associated to other research sources mapped the various mechanisms that preserve the economic and financial balance in those concessions. This analysis also revealed the legal controversies arising from said mechanisms. Some of these controversies are related to all, while others specifically concern particular mechanisms. This research demonstrated the importance of the contractual concession agreement clauses as well as the inappropriateness of establishing general ideas on the economic and financial balance of concession agreements. The true substance of this matter can only be inferred from the contractual rules and their daily application. The mere analysis of the statutory law and theories disconnected from the daily practices turn the verification of the actual substance of economic and financial balance of concessions impossible